Humor against Vargas: communist drawings from the election campaign period to suicide (1950-1954) (Revista Tempo e Argumento, 2016)
This article aims to analyze the editorial cartoons and caricatures on Getúlio Vargas published by the communist press within the period from Vargas’ election campaign to his suicide (1950-1954), including the reaction of communists to this dramatic act. These images by the party press are usually relegated to the background by historiography, but they also express the ideology of the Brazilian Communist Party (PCB) and its reading of the national political reality. Thus, the characters observed in the drawings and their characterization are significant sources for understanding the communist reading of Getúlio Vargas and the context of that time. Keywords: Vargas, Getúlio, 1883-1954; Brazilian Communist Party; Caricature; Press – Brazil.